ANALISIS PERUBAHAN ALIRAN PANAS DENGAN MODIFIKASI BUKAAN TUNGKU RE-HEARTING PORTABEL UNTUK PRATIKUM LABORATORIUM TEKNOLOGI MATERIAL - Rama Febrian; Armila Armila; Rudi Kurniawan Arief (Ensiklopedia Research and Community Service Review, 2022)
Metallurgical furnaces are needed in the metal forming process, the furnaces that have been analyzed by Ongki prima widodo are only capable of reaching the highest temperature of 1400oC, with a long burning process, a modification was made by moving the furnace openings in a ratio of 30:70cm to 15:85cm. Changes in the position of the openings are expected to increase the heat flow to the compressor pressure rate, so that the heat flow easily propagates and the temperature rises. With changes in the position of the opening and enlargement of the hole, where the initial temperature of 300oC increases to 1432oC, with a time of 300 seconds, so that the rate of heat change is equivalent to the rate of change of compressor pressure of 38.6 km/h with a temperature change of 713oC. Testing the furnace with the addition of compressor pressure and measuring the rate of change of temperature. From the measurement results, the heat flow changes from 3000C to 14320C, within 30 seconds to 300 seconds. The results of data collection obtained air pressure (P) 18.2 km/h, 19.3 km/h, 20 km/h, 22.5 km/h, 38.6 km/h. The results of the analysis within 30s with an air pressure of 18.2 km/h obtained a temperature of 305.8oC an increase in temperature, 38.6 km/h air pressure obtained a temperature of 713.5oC, at a time of 300 seconds with an air pressure of 18.2 km/h. h obtained a temperature of 665.3oC the increase in temperature. Pressure 38.6 km/h obtained a temperature of 1110oC. This modification of the furnace opening changes can reach a final temperature of 1432°C.Keywords: furnace re-heating, heat transfer,temperature and forging.